OPTIMIZING THE QUALITY OF SUPERIOR EDUCATION IN DARUL HUDA STIES' COLLEGES THROUGH HR MANAGEMENT STRATEGIES - Rahayu, Puji (Journal of Social and Economics Research, 2024)
Improving the quality of education in the STIES Darul Huda Mesuji Lampung Sharia Economics study program is faced with human resource management (HR) challenges which include limited lecturer training, supporting infrastructure, and technological adaptation. This research aims to identify and analyze effective HR management strategies in improving the quality of education, with a focus on implementing competency-based recruitment, sustainable development through training, and integrating technology in the learning process. The research method used is a qualitative approach with a case study method, involving in-depth interviews, observation and document study. The research results show that although there are efforts in managing human resources, challenges such as uneven training and technological limitations are still the main obstacles. Implementation of a more structured HR management strategy, including transparent recruitment, continuous training, and application of sharia principles such as fairness and transparency, can significantly improve lecturer performance and education quality. Management support and investment in technology infrastructure is critical to support the sustainability of this strategy.